Analytical training in epidemiological research for Medicine students - José Aureliano Betancourt-Bethencourt; Luis Acao-Francois; Yanira González-Ronquillo (Universidad Nacional, Costa Rica, 2016)
The Medicine students need to increase their research skills. Therefore, there is a main goal to train the fifth year students in epidemiological analysis methods during educational activities in work hours. In the Tula Aguilera Health Area, the fifth year Medicine students conducted a control-case study, where they applied a 14 questions survey to 69 persons sick with infectious diarrhea during June to December 2013. The results were compared to those of 131 healthy persons. The survey collected demographic, environmental and lifestyle variables. For each factor found, odd ratios (OR) were determined and the behavior of the analyzed variables was compared in both groups with the logistic regression technique. The basic reproductive number (Ro) was determined considering its impact and a simulation was compared with the usual historical dispersion of those diseases. Among the results, the students were trained to gather information and to transfer data to Excel Worksheets to analyze causal relationships. The students, after analyzing, were able to establish that the surveyed population had a low risk perception, they were also able to establish and calculate differences between sick and healthy people; for instance, people who don't cover solid wastes and become sick have nearly three times more risk (OR=2.81; IC 1.34-6.03), moreover the students were able to demonstrate the presence of environmental hazards. They found that the survey was reliable and became familiar with the usage of the basic reproductive number and derived simulations. We conclude that the designed training allowed the students to increase their skills during the educational practices at work regarding the learning by doing research methodology. The trainig strategy is valid, sustainable, updated and of great value in the Medicine students instruction.